Visual Political Knowledge: A Different Road to Competence?. (8th October 2013) - Prior, Markus
Abstract : Even though visual images and television are ubiquitous in politics, surveys rarely use visuals to assess what people know about politics. I measure visual political knowledge in a series of experiments that ask otherwise identical questions using either relevant visual elements or words only. These experiments were embedded in two representative surveys of U.S. residents conducted in 2003 and 2008. Adding a visual to an otherwise identical knowledge question causes, on average, a small but significant increase in correct answers. Treatment effects are larger for a subset of the population: women, older people, the less educated, and people with a visual cognitive style all perform disproportionately better on visual knowledge questions. Validation shows that visual knowledge is as indicative of civic competence as verbal knowledge. Hence, traditional verbal-only questions miss a significant amount of political knowledge. Several population segments previously deemed ill-informed in fact store some political information visually.